Multiple Regression Analysis of Catalytic Dehydrogenation of Isopropanol in a Chemical Heat Pump System - KARACA ALBAYRAK, FATMA (WILEY-V C H VERLAG GMBH, 2015)
Chemical heat pump is a clean technology developed to upgrade the low-level thermal energy to upper levels and to store energy without losses caused by temperature differences. Multiple regression analysis of catalytic dehydrogenation of isopropanol was performed. The endothermic dehydrogenation of isopropanol was carried out under continuous boiling and refluxing conditions in order to study the enhancement effects of the presence of an alkaline compound and different types of catalysts at various concentrations in the reaction medium on the evolution rate of hydrogen. The factorial experimental design method was applied to understand better the coupled influences of both catalyst and alkaline additive concentrations to discuss and evaluate statistically the results for different catalysts and to develop the related models.
Keywords: Catalytic dehydrogenation; Chemical heat pump; Multiple regression analysis; THERMAL-ENERGY; 2-PROPANOL DEHYDROGENATION; REACTION COUPLE; ENHANCEMENT; HYDROGENATION; DESIGN